2002
DOI: 10.4269/ajtmh.2002.67.656
|View full text |Cite
|
Sign up to set email alerts
|

Detection and stability of Japanese encephalitis virus RNA and virus viability in dead infected mosquitoes under different storage conditions.

Abstract: Abstract. A semi-nested polymerase chain reaction (PCR) was evaluated for detection of Japanese encephalitis (JE) virus in infected mosquitoes stored under simulated northern Australian summer conditions. The effect of silica gel, thymol, and a combination of the two on RNA stability and virus viability in dead mosquitoes were also examined. While JE virus RNA was relatively stable in mosquitoes held for up to 14 days after death, viable virus was not detected after day 1. Thymol vapor inhibited fungal contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 25 publications
6
20
0
Order By: Relevance
“…Our data and those of others (Hall-Mendelin et al 2010, van den Hurk et al 2007 clearly showed that infectious mosquitoes expectorate flaviviruses while sugar feeding and that WNV RNA is relatively stable on sugar wicks for over 5 d at ambient temperatures, agreeing with previous laboratory experiments (Johansen et al 2002, Turell et al 2002.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data and those of others (Hall-Mendelin et al 2010, van den Hurk et al 2007 clearly showed that infectious mosquitoes expectorate flaviviruses while sugar feeding and that WNV RNA is relatively stable on sugar wicks for over 5 d at ambient temperatures, agreeing with previous laboratory experiments (Johansen et al 2002, Turell et al 2002.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the addition of the floral attractant phenyl acetaldehyde (Jhumur et al 2006(Jhumur et al , 2008 seemed to enhance the attraction of a 66% sucrose solution in desert habitats in the Coachella Valley, and we repeatedly were able to detect WNV RNA in sugar wicks exposed for a 5 d period. Our data and those of others (Hall-Mendelin et al 2010, van den Hurk et al 2007 clearly showed that infectious mosquitoes expectorate flaviviruses while sugar feeding and that WNV RNA is relatively stable on sugar wicks for over 5 d at ambient temperatures, agreeing with previous laboratory experiments (Johansen et al 2002, Turell et al 2002.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, time between the death of swans and the finding of their bodies and collection of tissues and their storage at -80°C was not known. As detectable concentrations of influenza viruses in tissue decrease more rapidly than their RNA content (Johansen et al, 2002), the detection of RNA in organs may often be the only source of information on viral infection. The proportion of viral RNA to live virus in a tissue cannot be assessed without comparison with an experimental infection.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,[16][17][18] We have extended these studies by providing a simple and highly effective method for preparation, storage, and transport of mosquito specimens removed from traps by field workers in locations geographically isolated from diagnostic facilities. We deliberately used rudimentary methods for preparing and applying the mosquito samples to the FTA cards which do not require specialized equipment.…”
mentioning
confidence: 99%